Attenuation of acute postoperative pain and opioid requirement with the use of magnesium sulfate in patients undergoing limb amputations - Qureshi, Rabeea Sajid; Alam, Tanveer; Khan, Ahsun Waqar; Muhammad Bilal Shafiq (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the effects of magnesium sulphate on the total dose of intravenous morphine consumption postoperatively following limb amputations along with rescue analgesia requirement, pain scores and side effects. Method: The prospective, triple-blinded, randomised controlled study was conducted from October 2021 to May 2022 at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised patients scheduled for limb amputations. They were randomised into 2 equal groups. The anaesthesia protocol was uniform for all patients. Intervention group A was administered 30mg/kg loading dose and 10mg/kg/hr maintenance dose of magnesium sulphate intravenously, while patients in control group B received the same amount of plain isotonic saline. Morphine consumption was measured for 24 hours postoperatively and included rescue analgesia, if required by the patient in the post-anaesthesia care unit, and patient-controlled analgesia. Numeric rating scale was used for the evaluation of postoperative pain in both groups at 15min, 1h, 2h, at discharge from the post-anaesthesia care unit and at 12h and 24h in the ward. Data was analysed using SPSS 23. Results: Of the 24 patients enrolled, the study was completed by 20(83.33%). There were 10(50%) patients in group A; 8(40%) males and 2(20%) females with mean age 24.8±14.14 years and mean surgery time 130.5±47.86 minutes. There were 10(50%) patients in group B; 8(40%) males and 2(20%) females with mean age 23.2±7.4 years and mean surgery time 117±23.85 minutes (p>0.05). Total morphine used over 24 hours in group A was 16±3.1mg compared to 29.6±11.2mg in group B (p<0.05). The time for first use of patient-controlled analgesia after arriving in the post-anaesthesia care unit was significantly delayed in group A 72.2±24.95 minutes compared to that in group B 25±26.68 minutes (p<0.05). Pain scores were significantly higher in the group B at 15min compared to group A (p<0.05), but not at the rest of the time points (p>0.05). Conclusion: Intravenous magnesium sulphate proved to be effective in lowering postoperative opioid requirement following limb amputations. Key Words: Postoperative pain, Analgesia, Amputation, Surgical amputation, N-methyl-D-aspartate receptors, Magnesium, Magnesium sulphate, Opioid analgesics, Morphine, Patient-controlled analgesia.